Use of Ultrasound‐Guided Small Joint Biopsy to Evaluate the Histopathologic Response to Rheumatoid Arthritis Therapy: Recommendations for Application to Clinical Trials. Issue 10 (23rd September 2015) - Humby, Frances; Kelly, Stephen; Hands, Rebecca; Rocher, Vidalba; DiCicco, Maria; Ng, Nora; Zou, Lu; Bugatti, Serena; Manzo, Antonio; Caporali, Roberto; Montecucco, Carlomaurizio; Bombardieri, Michele; et al.
Abstract : Objective: To examine in a cohort of rheumatoid arthritis (RA) patients undergoing serial ultrasound (US)–guided biopsies of small joints in the context of clinical trials whether sufficient synovial tissue could be obtained at both baseline and second biopsy to: 1) accurately evaluate the synovial immune phenotype, 2) permit adequate RNA extraction to determine molecular signatures, and 3) sensitively detect change in the number of synovial sublining macrophages (CD68+) following effective therapy. Methods: Synovial samples from RA patients undergoing US‐guided biopsy of small joints as part of 2 clinical trials (Barts Early Arthritis Cohort [n = 18] and the Clinical and Pathological Response to Certolizumab Pegol (CLIP‐Cert) study [n = 17]) were examined, and the quality and quantity of histologic samples and RNA extracted per joint were determined and compared to synovial thickness and power Doppler scores determined by US before biopsy. Modulation of the number of CD68+ sublining macrophages was correlated with clinical response to treatment. Results: Good quality synovial tissue that accurately reflected the synovial immune phenotype of the total joint was obtained in 80% of US‐guided procedures when synovial thickness (higher than grade 2) was documented before biopsy. In 100% of the procedures, sufficient RNA was extracted to permit molecular analysis. There was a significant correlation between change in CD68+ sublining macrophage number and clinical response to treatment. Conclusion: This study provides minimum standards for sample retrieval for small joint biopsy. Furthermore, our findings confirm the clinical utility of the procedure in the largest reported cohort of US‐guided small joint biopsies. The demonstration that small joint synovial tissue can be readily accessed by a technically simple, minimally invasive procedure is likely to facilitate critical advancements in the knowledge of RA pathobiology and personalized health care.